At Tahlil At Taqabuli (Contrastive Analysis) Vocabulary in Indonesian and Arabic - Azisi; Faisal Faliyandra (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
Abstract The purpose of this study is to describe the differences between Indonesian vocabulary and Arabic based on time, number, persona and sentence structure. The method in this study is synchronous plosive. The research is based on three stages, namely (1) The data provision phase, (2) The data analysis stage, and (3) the presentation stage of the data analysis results. This research Data is a vocabulary that shows the meaning of time, number, persona, and sentence structure in Bahasa Indonesia and Arabic. The results of the study are the difference forms between Indonesian vocabulary and Arabic based on times, numbers, and persona. At the level of time, there is a difference in the past, nowadays, and times will come. At the level of the number there are differences in the number of singularist and pluralist numbers. Then, at the persona, there is a difference of first-person persona, a second-person persona, and a third-person persona. In the sentence structure there are differences that generally located in the subject/Fa'il. The subject is ahead in the sentence structure in B1, but the subject or Fa'il in B2 is located in the second order (in the past) and in the first order (in the medium). Abstrak Tujuan dari penelitian ini adalah untuk mendeskripsi perbedaan bentuk kosakata bahasa Indonesia dan bahasa Arab berdasarkan kala, jumlah, persona dan struktur kalimat. Metode yang digunakan dalam penelitian ini adalah sinkronis kontrastif. Kemudian, penelitian ini didasarkan pada tiga tahap, yaitu (1) tahap penyediaan data, (2) tahap analisis data, dan (3) tahap penyajian hasil analisis data. Data penelitian ini adalah kosakata yang menunjukkan makna kala, jumlah, persona dan struktur kalimat dalam bahasa Indonesia dan bahasa Arab. Hasil penelitian berupa perbedaan bentuk kosakata bahasa Indonesia dan bahasa Arab berdasarkan kala, jumlah, dan persona. Pada tataran kala terdapat perbedaan kala lampau, kala sekarang, dan kala akan datang. Pada tataran jumlah terdapat perbedaan jumlah singularis dan jumlah pluralis. Kemudian, pada tataran persona terdapat perbedaan persona orang pertama, persona orang kedua, dan persona orang ketiga. Dalam struktur kalimat terdapat perbedaan yang pada umumnya terletak pada subyek/fa’il. Subyek berada di depan dalam struktur kalimat dalam B1, namun subyek atau fa’il dalam B2 terletak di susunan kedua (dalam kala lampau) dan pada susunan yang pertama (dalam kala sedang). Kata kunci: kala, kata, persona, struktur kalimat, analisis kontrastif